Foreign policy reorientation: Feminist foreign and development policy in ministerial documents and debates - Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2023)
On 1 March, federal ministers Annalena Baerbock and Svenja Schulze jointly presented the Guidelines for a Feminist Foreign Policy (FFP) of the Federal Foreign Office (AA) and the Strategy for a Feminist Development Policy (FDP) of the Federal Ministry for Economic Cooperation and Development (BMZ). Despite coordination between the two ministries and similar consultations with civil society, the ministers presented documents that differ in form and content and also draw on feminist approaches to varying degrees. Together, however, they have initiated a debate in Germany on the goals and means of international policy. In order for the desired cultural and systemic change to go beyond gender equality, a broader inter-ministerial effort is needed.
Keywords: 320; Feminismus; Menschenrechte; patriarchale Strukturen; Gleichstellung; Gender-Mainstreaming; Frauenrechtskonvention; CEDAW; Diskriminierung; Marginalisierung; Gender Pay Gap; LSBTIQ; sexualisierte Gewalt; Affirmative Action; Feminist foreign and development policy; discrimination; LGBTIQ*; Annalena Baerbock; Svenja Schulze; Guidelines for a Feminist Foreign Policy (FFP); UN Convention on the Elimination of All Forms of Discrimination against Women (CEDAW); UN Women; Peace and Security (WPS)